2018
DOI: 10.1002/jbm.b.34177
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun fibroin/polyurethane hybrid meshes: Manufacturing, characterization, and potentialities as substrates for haemodialysis arteriovenous grafts

Abstract: Several attempts made so far to combine silk fibroin and polyurethane, in order to prepare scaffolds encompassing the bioactivity of the former with the elasticity of the latter, suffer from critical drawbacks concerning industrial and clinical applicability (e.g., separation of phases upon processing, use of solvents unaddressed by the European Pharmacopoeia, and use of degradable polyurethanes). Overcoming these limitations, in this study, we report the successful blending of regenerated silk fibroin with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…So far, there are many papers about SF-PU composite materials to use them as biomaterials. 13,25,[28][29][30][31][32][33][34][35][36][37]57,58 commercially available biomedical grade segmented PU by wet spinning method, which has potential as a fiber for artificial vascular graft. 28 The small-diameter tubular artificial vascular graft was prepared from the HFIP solutions of SF-biomedical grade segmented PU mixture by electrospinning method by us.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, there are many papers about SF-PU composite materials to use them as biomaterials. 13,25,[28][29][30][31][32][33][34][35][36][37]57,58 commercially available biomedical grade segmented PU by wet spinning method, which has potential as a fiber for artificial vascular graft. 28 The small-diameter tubular artificial vascular graft was prepared from the HFIP solutions of SF-biomedical grade segmented PU mixture by electrospinning method by us.…”
Section: Discussionmentioning
confidence: 99%
“…The electrospinning methods have been used widely for the application of the SF-PU composite materials in biomedical field. 13,[29][30][31][32] The SF-PU composite films were also prepared by physical blending method. 25,[34][35][36][37]58 The characterization of the SF-PU composite materials by FT-IR and X-ray diffraction analyses suggested that there are no specific interactions between SF and PU, implying molecular immiscibility and phase separation in these materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] In situ tissue engineering strategies, using acellular, totally or partially degradable, scaffolds that are gradually replaced/remodeled by the host, might represent a viable alternative, joining the main advantage of synthetic grafts (i.e., early puncturability) and the ones of biological substitutes (higher compatibility, remodeling capability, higher patency rates). [4][5][6] In this context, we have previously developed an electrospun hybrid vascular graft based on the combination of natural silk fibroin and synthetic poly-carbonate urethane (a blend named Silkothane), [7] which proved to be a potential candidate for an in situ engineering approach to arteriovenous shunting, due to its favorable mechanical properties, suitable permeability, nonhemolytic character, long clotting time, capability of sustaining adhesion of human umbilical vein endothelial cells in vitro, and early cannulation potential. [8] Indeed, the validation of any in situ tissue engineering products, being their performances so much dependent on the host reaction, needs to face in vivo testing early in the product development pipeline, to assess safety and feasibility of implantation, as well as to preliminarily evaluate the outcomes of grafting in a clinically relevant setting.…”
Section: Introductionmentioning
confidence: 99%
“…Scaffolds derived from Bombyx mori silk fibroin (referred to as “silk” throughout) have been used to engineer a number of tissues including heart, bone, cartilage, arteriovenous grafts, esophagous, nerve, urethra, and liver . Silk‐based biomaterials show great promise in regenerative medicine applications, but rapid vascularization of large, 3D silk constructs remains challenging.…”
Section: Introductionmentioning
confidence: 99%